Utility Privatization and Regulation 2003
DOI: 10.4337/9781781951316.00017
|View full text |Cite
|
Sign up to set email alerts
|

The reform of the utilities sector in Argentina

Abstract: The Privatization of the national public utilities that took place almost a decade ago in Argentina seem to be explained by the persisting deficits of the enterprises, a general dissatisfaction with their performance and the difficulties government faced in their control. During the period of private management, companies restructured their revenues by both regrouping consumers and raising their two-part tariffs unevenly, increased the number of customers and achieved perceptible quality improvements. For asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 3 publications
0
26
0
1
Order By: Relevance
“…• Low-income groups: The evidence is not conclusive on whether the poorest income groups have been better or worse off (Delfino and Casarin, 2001;.Ennis and Pinto, 2002;Chisari et al 1997). …”
Section: Case Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…• Low-income groups: The evidence is not conclusive on whether the poorest income groups have been better or worse off (Delfino and Casarin, 2001;.Ennis and Pinto, 2002;Chisari et al 1997). …”
Section: Case Studiesmentioning
confidence: 99%
“…• Improved access: Policies aimed at improving access to service can be effective and combined with privatisation (Ennis and Pinto, 2002;Delfino and Casarin, 2001). …”
Section: Case Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A paper that supports our conjecture about the occurrence of regressive redistribution is Delfino and Casarin (2003), who analyze the change in the consumer surplus in Argentina. The authors found that low-income households were particularly damaged because of the increases in fixed charges in the utilities.…”
Section: Existing Empirical Research On the Redistribution Effects Ofmentioning
confidence: 74%